Zoledronic acid in metastatic osteosarcoma: encouraging progression free survival in four consecutive patients. Issue 1 (December 2016) - Conry, Robert; Rodriguez, Michael; Pressey, Joseph
Abstract Background Zoledronic acid (ZA) is a third-generation bisphosphonate in widespread clinical use to reduce pain and skeletal events in patients from a variety of malignancies with bone metastases. Pre-clinical studies indicate that ZA inhibits osteosarcoma through direct anti-proliferative effects, immune activation and anti-angiogenic activity. Methods The purpose of this study was to evaluate the antitumor efficacy of ZA at standard dose until progression in patients with stage IV osteosarcoma lacking a standard of care treatment option proven to influence survival. Researchers retrospectively reviewed medical records of all patients at our institution with high-grade osteosarcoma presumed to be incurable due to metastases progressive after primary combination chemotherapy who received single agent ZA in an effort to delay progression. Results In our four-patient cohort following initiation of ZA, the median progression-free survival was 19 months, and median overall survival was 56+ months. Two of four patients have remained progression-free since starting ZA. The other two initially progressed after 18–20 months on ZA followed by metastasectomy of lung or dural metastases and further stability for over a year following resumption of ZA. After a 20-month progression-free interval on ZA alone, one patient had partial response following addition of pazopanib to ZA that likely contributed to long term disease control. The four patients experienced no significant toxicities despite protracted dosing of ZA for up to 5 years, and none have required chemotherapy since beginning ZA. Conclusions Single agent ZA was associated with encouraging progression-free survival in four consecutive patients with metastatic osteosarcoma. Prospective trials of single agent ZA are warranted as protracted maintenance therapy in surgically incurable osteosarcoma relapsed or refractory to first line combination chemotherapy with radiographically measurable metastases.